Transatlantic food and agricultural trade policy 50 years of conflict and convergence - Josling, Timothy E.; Tangermann, Stefan; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2015)
Tim Josling and Stefan Tangermann's Transatlantic Food and Agricultural Trade Policy traces the past fifty years of transatlantic trade relations in the area of food and agricultural policy, from early skirmishes over farm policies to on-going conflicts over biotech foods and hormone use in animal rearing. The authors take an analytical approach to the causes of transatlantic conflict and the extent to which these trade tensions in agricultural markets have reflected wide differences in policy approaches and levels of support. They explore the role played by international rules, in the GATT, and subsequently the WTO, in disciplining farm price support policies to allow for more open markets. The book also points to possible ways to end five decades of transatlantic trade tensions in the area of food and farm products. Scholars, practitioners and policymakers will find this timely book an invaluable and comprehensive guide to the causes of, and solutions to, the persistent EU-US trade conflicts in agricultural and food policy.
1. The emergence of transatlantic agricultural tensions (1957 to 1971) -- 2. Turbulent markets and increasing trade conflicts (1972 to 1985) -- 3. The adoption of disciplines and the domestic reforms (1986 to 2001) -- 4. Growing challenges to US and EU farm policies (2001 to 2014) -- 5. Food policy moves to center stage in transatlantic relations (1986 to 2013) -- 6. The Transatlantic Trade and Investment Partnership and the path to convergence (2011 to 2014 and beyond) -- 7. Lasting conflict or eventual convergence?
Includes bibliographical references and index.
Description based on online resource; title from title screen (viewed May 13, 2015).
Keywords: Produce trade -- Government policy -- European Union countries; Produce trade -- Government policy -- United States; Agriculture and state -- European Union countries; Agriculture and state -- United States; European Union countries -- Foreign economic relations -- United States; United States -- Foreign economic relations -- European Union countries; Electronic books